Students, temporary workers and co-op workers: An experimental investigation on social preferences - Davide Dragone; Fabio Galeotti; Raimondello Orsini (Games, 2015)
We conduct an artefactual field experiment to compare the individual preferences and propensity to cooperate of three pools of subjects: Undergraduate students, temporary workers and permanent workers. We find that students are more selfish and contribute less than workers. Temporary and permanent contract workers have similar other-regarding preferences and display analogous contribution patterns in an anonymous Public Good Game.
Keywords: C72; C93; D23; H41; J54; 330; temporary worker; decomposed game technique; dictator game; public good game; experiment